Confined crystallization in the binary blends of diblock copolymers bearing stereoisomeric isotactic and syndiotactic polypropylene. Issue 6 (2nd November 2021) - Chu, Che‐Yi; Chen, Meng‐Zhe; Li, Wun‐Hong; Tsai, Jing‐Cherng; Chen, Hsin‐Lung
Abstract: The morphology and crystallization behavior of the binary blends of two crystalline‐amorphous diblock copolymers bearing stereoisomeric crystalline blocks have been investigated. A polystyrene‐ block ‐isotactic polypropylene (S‐iPP) and a polystyrene‐ block ‐syndiotactic polypropylene (S‐sPP) were used to prepare a series of blends forming lamellar morphology. In the melt state, the PS blocks from these two diblock copolymers mixed intimately in the PS lamellar microdomains; meanwhile, the iPP and sPP blocks were found to form a miscible mixture in the PP domains. Under the effects of nanoscale confinement and the constraint imposed by the junction points, the iPP and sPP blocks exhibited the crystallization behavior greatly deviated from that in the neat diblock copolymers. A local demixing between a fraction of iPP and sPP chains was found to occur in the S‐sPP‐rich blend at low crystallization temperatures, which yielded the defective crystalline domains composed of alternately intervened iPP and sPP crystallites. This crystalline species displayed a significant depression of melting point located at the temperature around 10°C higher than the corresponding T c due to an excess surface free energy at the interface between the alternately intervened iPP and sPP crystallites. Abstract : A miscible mixture of stereoisomeric isotactic and syndiotactic polypropylene (iPP and sPP) block chains confined within the common lamellar microdomains formed highly defective crystalline domains, in which iPP and sPP crystallites intervened each other. These crystallites exhibited low melting points due to an excess surface free energy.